2022
DOI: 10.3390/ijms23126586
|View full text |Cite
|
Sign up to set email alerts
|

Manual Therapy Facilitates Homeostatic Adaptation to Bone Microstructural Declines Induced by a Rat Model of Repetitive Forceful Task

Abstract: The effectiveness of manual therapy in reducing the catabolic effects of performing repetitive intensive force tasks on bones has not been reported. We examined if manual therapy could reduce radial bone microstructural declines in adult female Sprague–Dawley rats performing a 12-week high-repetition and high-force task, with or without simultaneous manual therapy to forelimbs. Additional rats were provided 6 weeks of rest after task cessation, with or without manual therapy. The control rats were untreated or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…This would be consistent with findings from another study in which we examined the effects of 6 weeks of rest, with or without a manual therapy treatment, after a 12‐week task period. [ 31 ] We found that rest (alone or combined with manual therapy) effectively rescued the osteoclastic response but did not improve osteoblastic numbers or activity or already established task‐induced loss in trabecular bone volume fraction. [ 31 ] Only the anti‐CCN2 treatment during rest improved the task‐induced trabecular bone loss.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This would be consistent with findings from another study in which we examined the effects of 6 weeks of rest, with or without a manual therapy treatment, after a 12‐week task period. [ 31 ] We found that rest (alone or combined with manual therapy) effectively rescued the osteoclastic response but did not improve osteoblastic numbers or activity or already established task‐induced loss in trabecular bone volume fraction. [ 31 ] Only the anti‐CCN2 treatment during rest improved the task‐induced trabecular bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] We found that rest (alone or combined with manual therapy) effectively rescued the osteoclastic response but did not improve osteoblastic numbers or activity or already established task‐induced loss in trabecular bone volume fraction. [ 31 ] Only the anti‐CCN2 treatment during rest improved the task‐induced trabecular bone loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations